The Coupling Coordination Relationship between Economic Upgrading and Social Upgrading in the Cities of the Pearl River Delta and Its Influencing Factors - Cai Bowei; Xing Zuge; Zhou Jin; Huang Gengzhi (Redai dili, 2022)
As economic globalization deepens, academic attention has shifted from the pattern and spatial organization of global production to the important participants of globalization: workers. Existing studies pay much attention to the added value and profits from economic upgrading in the process of globalization. Few works examine the improvement of workers' employment quality and social participation level brought about by social upgrading. In particular, there is a shortage of research on the relationship between economic upgrading and social upgrading. To further explore the relationship and synchronous process between these two and provide policy implications to help promote the type of upgrading that benefits the majority of workers rather than a small number of enterprise owners, this study adopts the entropy value method to comprehensively compare the characteristics of economic and social upgrading in the Pearl River Delta (PRD) region in South China from 2006 to 2019. It uses the improved coupling coordination model to quantitatively measure the coupling degree and coupling coordination degree of economic and social upgrading, and analyzes the factors affecting the coupling coordination degree based on several panel data regression models. The results are as follows. First, the process of economic and social upgrading in the PRD from 2006 to 2019 shows a fluctuating upward trend overall. The global financial crisis and the local industrial transformation in the region are important factors affecting the process of economic and social upgrading. Second, the overall coupling degree of the economic and social upgrading in the PRD during 2006-2019 shows a U-shaped evolution, changing from a high-level coupling stage down to a running-in stage and then up to a high-level coupling stage. Third, from 2006 to 2019, the coupling coordination degree in the PRD shows an overall increasing trend. This period saw improved coordination between the economic upgrading system and the social upgrading system. Finally, the level of regional human capital, consumption demands, foreign investment, and public governance have positive effects on the degree of the coupling coordination of economic and social upgrading in the PRD, while environmental pollution has a negative effect. This study contributes to the existing literature on social upgrading by integrating economic and social upgrading into the framework of regional development and revealing the coupling and coordination relationship between economic and social upgrading. The results advance our understanding of the relationship between economic and social upgrading and explores the policy implications for promoting regional economic and social development. Enhancing workers' human capital, increasing consumption demands, attracting global capital, and strengthening public governance are likely to stimulate the role of economic upgrading in promoting social upgrading.